HIV and Maternal‐Fetal Immunity: Challenges and Strategies for Reducing Vertical Transmission‐A Narrative Review - Emmanuel Ifeanyi Obeagu (Health Science Reports)
ABSTRACT Background and Aims Mother‐to‐child transmission (MTCT) of HIV remains a significant global health challenge, particularly in resource‐limited settings. The virus disrupts maternal‐fetal immunity through immune dysregulation, placental barrier impairment, and altered antibody transfer, thereby increasing the risk of vertical transmission. Methods and Results This narrative review synthesizes current evidence on the immunological and clinical factors influencing MTCT. It highlights how maternal immune exhaustion, placental inflammation, and suboptimal ART timing contribute to transmission. While widespread use of ART has reduced MTCT rates, persistent challenges include late ART initiation, HIV drug resistance, co‐infections, and transmission through breastfeeding. Emerging strategies—such as maternal immune modulation, monoclonal antibody therapies, and tailored ART regimens—show potential for further risk reduction. Conclusion To effectively minimize MTCT, comprehensive prevention approaches are essential. These should combine medical interventions with maternal nutrition support, co‐infection management, and safe breastfeeding practices under ART coverage. A multifaceted strategy is key to protecting both maternal and infant health.